AN EVALUATION OF ENGLISH PROGRAM: A DEEP ANALYSIS OF EFL LEARNERS’ ATTITUDE TOWARDS ENGLISH PROGRAM - Sari, Maria Puspa (IJIET (International Journal of Indonesian Education and Teaching), 2021)
This study investigated EFL learners’ attitude towards English program conducted by the language institute in an engineering college in Palembang. The program consisted of 36 regular meeting where participants learn English for their field and TOEFL test. This evaluation was conducted at the end of the program to advance the English program in the college to meet their learners’ of English. As a part of evaluation, this study evaluated six aspects in program namely teaching materials, teaching methodology, course fee, course design, facilities and service provided in the program. The participants of this study were 87.9% learners who took English course in the institute. A questionnaire consisting 15 items was given to the participants at the end of the program. This study revealed that most participants had positive attitude towards the English program provided by the language institute. Clearly, they were satisfied with the English program in the college.